Hubungan Tingkat Pengetahuan Lansia dengan Perilaku Pencegahan Penularan Covid 19 di Desa Pantirejo Kecamatan Kasesi - Haryanti, Suci; widhiastuti, ratna; Widyantoro, Wisnu (Jurnal Indonesia Sehat, 2024)
Background: Coronavirus is a family of coronaviridae viruses because it has a wreath-shaped protrusion on the viral envelope. A new type of coronavirus, namely Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) attacks the respiratory system causing pneumonia.Lack of knowledge about the Covid-19 pandemic can lead to various kinds of speculation about the spread of the Corona virus. So the government needs to provide good information about the Covid-19 pandemic. The best way to control and prevent this disease is to break the chain of the spread of COVID-19. Breaking the chain of transmission can be carried out by implementing health protocols in a disciplined manner, namely by frequently washing hands with running water and soap or using hand sanitizers, using masks and not touching the face area before washing hands, and keeping a distance in every activity or what is known as the 3M. Methods: This research is a quantitative study with a research design using a cross sectional approach. The sampling technique used is non-probability sampling with random sampling type and the sample size is 50 people. Results: The results of data analysis using the Kendall's Tau-b statistical test show a P value of 0.004 < 0.005 which indicates Ho is rejected and Ha is accepted or there is a relationship between the level of knowledge of the elderly and the behavior of preventing transmission of COVID 19. The elderly are expected to know knowledge about COVID 19 and its prevention.